Optical characteristics of 1.55 μm GaInNAs multi-quantum wells - Sun, Handong (2009)
We report the optical characterization of high-quality 1.55 mum GaxIn1-xNyAs1-y multiquantum wells (MQWs), grown on GaAs with Ga(In)N0.01As spacer layers. The transitions between the quantized QW states of the electrons and holes have been identified using photoluminescence excitation spectroscopy. Their energies are consistent with theoretical fitting based on the band anticrossing model. It is also confirmed by detailed spectroscopic measurements that the addition of even a small amount of In to GaN0.01As barriers remarkably improves the optical characteristics of the QWs. The results imply that although strain-compensated GaInNAs MQWs provide a feasible approach to realizing 1.55 mum optical emission, the relative lattice mismatch between the wells and barriers is critical to the optical quality of the related QWs.